Time-dependent self-association of spruce galactoglucomannans depends on pH and mechanical shearing. (May 2020) - Bhattarai, Mamata; Valoppi, Fabio; Hirvonen, Sami-Pekka; Hietala, Sami; Kilpeläinen, Petri; Aseyev, Vladimir; Mikkonen, Kirsi S.
Abstract: The demand for naturally derived, functional and cost-effective raw materials for various food applications is escalating. Spruce wood is a sustainable and abundant, but underutilized source of novel hydrocolloids—galactoglucomannans (GGM). Pressurized-hot water extracted GGM with an intermediate molar mass are hypothesized to form colloidal solutions. To design superior quality products from GGM, an understanding of their colloidal stability and their potential effect in multiphasic systems is required. The present study addresses the functionality of GGM by characterizing their properties in a bi-phasic system, and for the first time, their time-dependent colloidal stability at different extrinsic conditions— pH, ionic strength and after the application of high-intensity mechanical shearing. Amongst the conditions studied, the colloidal stability of aqueous GGM solution was highly pH dependent. The results showed that an intermediate molar mass polysaccharide like GGM formed inter-/intra molecular assemblies, which grew over time, depending on the composition and processing of the aqueous medium. The molecular dispersion of GGM and their dynamic behavior was also compared to solutions of known food hydrocolloids—gum Arabic and hydroxypropylmethyl cellulose. The observed solution properties explain the hydrocolloid functionality of GGM and contribute to design of colloidal polysaccharide systems in food application. Graphical abstract: Image 1 Highlights: Colloidal stability of spruce galactoglucomannans (GGM) at different solution conditions was studied. GGM was in aggregated state at both acidic and alkaline pH, and high-pressure mechanical shearing destructured GGM assemblies to some extent. GGM exhibited time-dependent association even after the destructuring. Kinetics of association was pH dependent; ionic strength did not have significant role. Colloidal behavior of GGM was unique compared to gum Arabic and hydroxypropylmethyl cellulose.